Studies in Asian Nervilia (Nervilieae, Epidendroideae, Orchidaceae) VI: N. mekongensis, a new species from Thailand, Cambodia, Laos and Vietnam - Gale, Stephan W.; Schuiteman, André; Watthana, Santi; Sando, Tomoki; Souvannakhoummane, Keooudone; Averyanov, Leonid; Suddee, Somran (Phytotaxa, 2016)
A new species of the terrestrial orchid genus Nervilia is described and illustrated from material collected at several localities in the Greater Mekong region of Southeast Asia. The multi-flowered inflorescence bearing relatively large flowers with a pubescent lip, and the many-veined, cordate-reniform leaf blade that is held well above ground level, place N. mekongensis in section Nervilia. Despite being superficially similar to N. aragoana, a widespread species of tropical Asia and Australasia, it is most closely affiliated to N. fordii, a species known from southern China and Thailand. It is distinguished by its stout inflorescence and lip that is broadest midway along the hypochile and which has acute, forward-projecting side-lobes and a short, ovate mid-lobe. A conservation assessment plus taxonomic notes are provided.